UMP honours and celebrates 9 retirees - Nor Salwana, Mohammad Idris (2020)
Pekan, 6 August 2020 - Retirement is definite for every civil servant, and many remarkable experiences, memories, and challenges, as well as a lot of knowledge, can be shared with the community.